Knowledge and Practices Regarding Deep Venous Thrombosis (DVT) Prevention Among Nurses in Jeddah, Saudi Arabia - Ruba M. Alharazi; Raiannah H. Alqahtani; Rahaf A. Alanazi; Walaa Alharbi; Shmokh M. Alshenen; Aisha Alhofaian; Afnan Tunsi; Loujain Sharif (Nursing Reports)
Background/Objectives: Deep venous thrombosis (DVT), the formation of a blood clot within a large vein, is one of the most common problems among hospitalized patients. The annual prevalence of DVT is 48 per 1,000,000. Nurses’ knowledge significantly affects compliance with VTE risk assessment and prevention. This study aimed to assess the knowledge and practices regarding deep venous thrombosis prevention among nurses in Ministry of Health hospitals and King Abdulaziz University Hospital (KAUH), Jeddah, Saudi Arabia. Methods: This study was conducted in Jeddah using a quantitative, descriptive, cross-sectional design. A sample of 240 registered nurses were conveniently recruited to complete a self-administered online questionnaire. The data were coded and analyzed through SPSS version 24. Results: The participants had adequate knowledge on the prevention of DVT (75.64 ± 18.88), and the highest level was observed for knowledge about the prevention and prophylaxis of DVT (81.98 ± 45.73%). The practice level of nurses in preventing DVT was 71.92%, with a mean score of 18.7. Conclusions: There is a significant effect of nurses’ level of academic qualifications, working ward, and DVT prevention training on their knowledge and practice of DVT prevention.